PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA PADA MATA PELAJARAN PPKn KELAS II - Herlin Herlin; Moh. Farid Nurul Anwar; Chusnul Chotimah (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
This research and development aims to create a valid and effective canva-based interactive learning media for Civics subjects in class II SDN Merjosari 3 Malang City. This study uses the research and development (RD) research type of the Borg and Gall model. The development procedure consists of nine steps modified from the Borg and Gall model: (1) research and data collection; (2) planning; (3) initial product development; (4) validation test; (5) product revision; (6) small group trial; (7) product revision; (8) large group trial; and (9) valid and effective products. The results of the final test with a score of 72 with an effective category can be seen from the benchmark reference assessment guidelines. These results show that canva-based interactive learning media in Civics class II subjects can be used as an effective and valid learning media.